A Two-Component Compliance and Ethics Program Model: An Empirical Application to Chilean Corporations - Majluf, Nicolas S. 1945-; Navarrete, Carolina M. (2011)
The rise of ethical scandals in the business world urged corporations to allocate time and resources to emphasize the ethical behavior of their managers and employees. The Model of Ethical Behavior in this article has three main assumptions: (1) the institutionalization of a Compliance and Ethics Program Model is done in terms of just two components: one Explicit and the other Implicit, (2) both components have a significant and direct influence over the ethical behavior of employees, which is represented in the model by two variables: Value Consistency and Presence of Ethical Conflicts, and (3) proper ethical behavior is perceived by employees to have a positive impact over the economic results of the firm. Reliable scales are developed to measure all these variables from the data collected by the “Barómetro de Valores y Ética Empresarial©,” a survey applied in 2009 to 12,321 employees from 54 Chilean corporations. The empirical analysis showed that there are three very distinctive components in the Presence of Ethical Conflicts variable: (1) what the company does that affects the employee, (2) what the company does that affects other people, and (3) what the employee does that affects the company. Finally, the Explicit and Implicit components of a Compliance and Ethics Program are shown to have a significant and positive impact over: (1) Value Consistency in employees’ behavior; (2) the Presence of Ethical Conflicts in organizations; and (3) the perceived importance of ethics as a key factor to improve economic performance.
Keywords: ethical model; Ethical Behavior; Explicit; Implicit; institutionalizing ethics